Quartz Reference Materials for Oxygen Isotope Analysis by SIMS. Issue 1 (16th September 2016) - Seitz, Susanne; Baumgartner, Lukas P.; Bouvier, Anne‐Sophie; Putlitz, Benita; Vennemann, Torsten
Abstract : Two quartz samples of igneous origin, UNIL‐Q1 (Torres del Paine Intrusion, Chile) and BGI‐Q1 (Shandong province, China), were calibrated for their oxygen isotope composition for SIMS measurements. UNIL‐Q1 and BGI‐Q1 were evaluated for homogeneity using SIMS. Their reference δ 18 O values were determined by CO2 laser fluorination. The average δ 18 O value found for UNIL‐Q1 is 9.8 ± 0.06‰ and that for BGI‐Q1 is 7.7 ± 0.11‰ (1 s ). The intermediate measurement precision of SIMS oxygen isotope measurements was 0.32–0.41‰ (2 s ; UNIL‐Q1) and 0.40–0.48‰ (2 s ; BGI‐Q1), respectively. While less homogeneous in its oxygen isotope composition, BGI‐Q1 is also suitable for SIMS trace element measurements. Key Points: Two new quartz reference materials developed for oxygen isotope measurements by SIMS are documented. UNIL‐Q1 is recommended for high‐precision oxygen isotope measurements. BGI‐Q1 is less homogenous, but also suitable for trace element determination by SIMS. Both reference materials are available to be shared with the SIMS community.